INDIKATOR MAKROEKONOMI DAN PEMBANGUNAN KOTA BANDUNG - Santoso, Teguh; Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.06.TAHUN 2019DO - 10.24843/EEB.2019.v08.i06.p05, 2019)
The high rate of inflation has the potential to increase poverty because it can reduce people's purchasing power, where if inflation rises significantly it can shift the people who are categorized as not poor, become vulnerable to poverty, almost poor and even poor. The aims of this study are to analyze the development of macroeconomic indicators, namely inflation and economic growth that are associated with poverty levels in the city of Bandung. The methodology used in this study is descriptive analysis and the ARMA (autoregressive moving average) model. The results showed that the high inflation in the city of Bandung compared to national and West Java inflation carries its own burden for the economy of the community, where purchasing power will decrease when inflation rises significantly and will have an impact on people's welfare. Inflation in the city of Bandung is often due to the price of food commodities (volatile food inflation). In addition, the high economic growth in the city of Bandung is not directly proportional to the decline in poverty levels. This shows that the quality of economic growth in the city of Bandung has problems that need attention. Therefore, local government in their efforts to encourage economic growth must prioritize poverty reduction and inequality.